2002
DOI: 10.1161/01.atv.0000033514.79653.04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estrogen Plus Progestin on Progression of Carotid Atherosclerosis in Postmenopausal Women With Heart Disease

Abstract: Objective-The Heart and Estrogen/Progestin Replacement Study (HERS) found no overall effect of estrogen plus progestin (compared with placebo) on coronary event rates in 2763 postmenopausal women with established coronary disease (mean 4.1 years of follow-up). In addition to the events trial, a carotid ultrasound substudy was established in 1993 to be conducted concurrently to determine whether hormone therapy affects the progression of the underlying atherosclerotic process. Methods and Results-Within the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 40 publications
4
26
1
2
Order By: Relevance
“…Consider also the report of the neutral effect of HRT on the progression of carotid atherosclerosis. 62 This result is dissonant with the fact that women using active HRT had a poorer clinical outcome, perhaps related to other actions of HRT not affecting atherosclerosis. Thus, despite examples of concordance between outcome trials and carotid atherosclerosis regression trials, the net benefit of any given therapy is determined by a variety of factors that may not be reflected in changes or lack of changes in carotid IMT.…”
Section: Evidence That Carotid Imt Tracks Regression/is a Guide To Thmentioning
confidence: 95%
See 1 more Smart Citation
“…Consider also the report of the neutral effect of HRT on the progression of carotid atherosclerosis. 62 This result is dissonant with the fact that women using active HRT had a poorer clinical outcome, perhaps related to other actions of HRT not affecting atherosclerosis. Thus, despite examples of concordance between outcome trials and carotid atherosclerosis regression trials, the net benefit of any given therapy is determined by a variety of factors that may not be reflected in changes or lack of changes in carotid IMT.…”
Section: Evidence That Carotid Imt Tracks Regression/is a Guide To Thmentioning
confidence: 95%
“…3,[52][53][54] Carotid IMT has been used as an end point in clinical trials of several drug classes, including lipid-lowering drugs, [55][56][57][58][59] antihypertensive agents, 60,61 and hormone replacement therapy (HRT). 62 However, use of change in surrogate end points to predict clinical outcome is statistically and mechanistically complex. Many studies show that statins reduce events and reduce carotid atherosclerosis.…”
Section: Evidence That Carotid Imt Tracks Regression/is a Guide To Thmentioning
confidence: 99%
“…[2][3][4] Randomized trials have provided variable results. Trials using conjugated estrogens with medroxyprogesterone acetate, 5 estradiol with gestodene, 6,7 and estradiol with norgestrel 8 found no effect on carotid or femoral artery intimamedia thickness. In contrast, unopposed estradiol did reduce progression of ultrasonographic carotid disease.…”
mentioning
confidence: 98%
“…The administration of estradiol has also been demonstrated to increase FMD compared with hormone-suppressed values (5,10,11,25,26,47). However, cardiovascular responses to different types of exogenous progestogen administration widely vary (1,7,23,36). Our laboratory has previously shown that levonorgestrel, desogestrel, and medroxyprogesterone acetate (MPA) all antagonized the effects of ethinyl estradiol on FMD (25,26,47).…”
mentioning
confidence: 99%